PWE-109 Cytoplasmic Expression of HMGB1 is Associated with Early Colorectal Carcinogenesis. (17th August 2016) - Hay, A; Christopoulou, CA; Murray, GI; El-Omar, EM; Hold, GL; McLean, MH
Abstract : Introduction: High Mobility Group Box-1 (HMGB1) is a ubiquitous nuclear protein that regulates gene expression. When phosphorylated, it translocates to the cytoplasm and extracellular space to stimulate pro-inflammatory responses and influence epithelial cell behaviour. Our aim was to assess expression of HMGB1 in colorectal neoplastic progression. Methods: Epithelial nuclear and cytoplasmic subcellular expression of HMGB1 was assessed immunohistochemically in a tissue microarray, representing 650 colorectal cancers and 50 paired normal colorectal mucosa samples, and 25 endoscopically resected paraffin embedded polyp cancer lesions (CaP), sourced from the Grampian Biorepository. Ethical approval was granted by the Grampian biorepository scientific committee. Intensity of HMGB1 expression (none, weak, moderate or strong) in all samples and proportion of positive cells/total CaP compartment (normal, adenoma, carcinoma) were double scored. Relative frequencies of staining across the tumour microarray were calculated and correlated to clinico-pathological data. In CaP, expression analysis used Fisher's exact test of 2X2 contingency tables. Results: Increased intensity of nuclear HMGB1 expression was correlated with increasing TNM tumour stage (p = 0.006) and Dukes stage (p = 0.016). Loss of nuclear HMGB1 intensity was identified at the early cancer stages compared to normal, followed by increased expression as the cancer progressed. No (p = 0.001) or low (p = 0.01) nuclear staining was associated with defective mismatch repair protein. Across the microarray, expression of cytoplasmic HMGB1 was significantly associated with malignancy (p < 0.0001). In CaP, both increased intensity and proportion of cytoplasmic expression was significantly associated with the area of carcinoma compared to adjacent normal (p < 0.0002) and adenoma (p < 0.0002). There was a significant reduction in proportion of nuclear HMGB1 positive cells in the CaP carcinoma compartment (p = 0.0001), due to foci displaying loss of nuclear and emergence of cytoplasmic HMGB1. The leading edge of cancer invasion had strong expression in both nuclear and cytoplasmic compartments (77% of CaP). Conclusion: Dynamic subcellular localisation of HMGB1 expression is associated with colorectal neoplastic progression with cytoplasmic HMGB1 a feature of early carcinogenesis. The functional impact of this warrants further investigation and may reveal new insight into the pathogenesis of colorectal cancer. Disclosure of Interest: None Declared